Public acceptance level towards modern biotechnology – a review / Muhammad Shafiq Sabidin - Sabidin, Muhammad Shafiq (Faculty of Plantation and Agrotechnology, 2019)
Modern biotechnology has been widely developed in recent years. The evolution of classical biotechnology into modern biotechnology has bring many changes in the world. Starting from fermentation into something more powerful today. Many researches have been done to ensure the safety and security of staple foods for the world consumptions is at maximum. This is due to increment of world population where it led to high demand of food supply. Due to that, modern biotechnology has been focusing on inventing crops that could meet the demand. Government of each contributed countries support the research in biotechnology financially in hope that researchers will be able to overcome many problems related with food production and in agriculture. Although with this many efforts have been done, the successfulness of commercialization is still depending on public acceptance towards the technology itself. In this review, have been focusing on both the level of public acceptance and the factors that control the levels. From the review, it has found that some of the countries were opposed with the implementation of biotechnology into daily life while some are agreed upon it. Few factors have been considered to explain the levels of acceptance including, (i) risk-benefit perception, (ii) religious beliefs and ethics, (iii) knowledge, awareness and trust and (iv) socio-psychological influences. By taking these factors into consideration, few examples of past models regarding the study have been use to explain the relationship between public acceptance levels and its factors.